Practice by postnatal care by the rural mothers, Bangladesh - Abdul Jabbar, Md.; Hoque, Syeda Rumana; Akter, Seikh Farid Uddin (Dhaka National Medical College and Hospital, 2009)
This descriptive cross-sectional study was at Sreepur upzilla of Bangladesh during the period of 6 months with the aim to find out the extend of utilization of postnatal care services by the rural mothers. A total of 250 women who had their last child born within 6 weeks to 6 months were selected systematically. Majority of the respondents were in age of 21 – 30 year (mean age 24.02 year± SD 6.45). Most of them (51.7%) were educated up to primary level having average family monthly income of Tk.6164/-(SD± 24.60/-). Of the total respondents 62.8% were married within 14-18 years of age which reflects the traditional practice of early marriage in rural area. Regarding mode of delivery 92.4% delivered normal vaginal delivery and most of them (92%) delivered at home. Among the respondents on 34% women received any sorts of postnatal care. Reasons for taking postnatal care were found as for self ailments (24%), child’s illness (16%), advice regarding diet (11.6%), advice regarding rest (11.2%), as routine health check up (8%). So it may be stated that in spite of availability of postnatal services utilization by the consumers is not up to satisfactory level. The factors responsible for non-utilization of postnatal services are illiteracy, lack of awareness, economical constraints and social custom and culture too.